The Relationship Between Massive Online Open Courses (MOOCs) Content Design And Students' Performance - Mohamad, Norhidayah; Othman, Azrina; Rajah, Neerosha; Ying, Tan Siew; Samsudin, Norsamsinar (Creative Commons Attribution Licence, 2021)
Over the years, there has been tremendous growth in online social networking which contributed to the revolution of higher education’s learning environment. Massive Online Open Courses (MOOC) is now common in online education, which provides open networks of self-directed learning. MOOCs are referred as a continuation trend in innovation that initiated by learning from geographical distance and online. MOOCs is a current evolvement in higher learning institution in Malaysia with the aims to provide quality education for the students. However, there are some challenges in developing effective instructional design courses and retaining learners in MOOCs. Therefore, the purpose of this study is to discover the relationship between MOOC’s content design and students’ performances among UTeM’s engineering students. Through literature review, variables are identified such as courses content design, enhancement in teaching and learning and students’ performance. In this study, 373 samples have been collected and the data analysed using SPSS. The results revealed that there are significant relationships between courses materials, courses activities, and courses tools with students’ performance. It is believed that this research paper will beneficial to higher education to improve MOOC’s content design in order to enhance the students’ performance in the future.